Application of BMP-2 and its gene delivery vehicles in dentistry - Valeriya Sergeevna Kuznetsova; Andrey Vyacheslavovich Vasilyev; Tatiana Borisovna Bukharova; Irina Alekseevna Nedorubova; Dmitry Vadimovich Goldshtein; Vladimir Karpovich Popov; Anatoly Alekseevich Kulakov (Saudi Dental Journal)
The restoration of bone defects resulting from tooth loss, periodontal disease, severe trauma, tumour resection and congenital malformations is a crucial task in dentistry and maxillofacial surgery. Growth factor- and gene-activated bone graft substitutes can be used instead of traditional materials to solve these problems. New materials will overcome the low efficacy and difficulties associated with the use of traditional bone substitutes in complex situations. One of the most well-studied active components for bone graft substitutes is bone morphogenetic protein-2 (BMP-2), which has strong osteoinductive properties. The aim of this review was to examine the use of BMP-2 protein and gene therapy for bone regeneration in the oral and maxillofacial region and to discuss its future use.